2016
DOI: 10.1523/jneurosci.1337-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Necessary Contributions of Human Frontal Lobe Subregions to Reward Learning in a Dynamic, Multidimensional Environment

Abstract: Real-world decisions are typically made between options that vary along multiple dimensions, requiring prioritization of the important dimensions to support optimal choice. Learning in this setting depends on attributing decision outcomes to the dimensions with predictive relevance rather than to dimensions that are irrelevant and nonpredictive. This attribution problem is computationally challenging, and likely requires an interplay between selective attention and reward learning. Both these processes have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…Accordingly, the impairment we observed on the 3-choice probabilistic learning task could result from a deficit in attentional selection, in learning, or in some combination of the two. A recent study in humans supports the idea of that VLPFC plays a role in attentional selection (Vaidya and Fellows, 2016). …”
Section: Discussionmentioning
confidence: 65%
“…Accordingly, the impairment we observed on the 3-choice probabilistic learning task could result from a deficit in attentional selection, in learning, or in some combination of the two. A recent study in humans supports the idea of that VLPFC plays a role in attentional selection (Vaidya and Fellows, 2016). …”
Section: Discussionmentioning
confidence: 65%
“…The task also had limited power to assess elemental multiattribute choices requiring trade-offs, limiting con-clusions about whether the VMF is also involved under those conditions. Interestingly, we found preliminary evidence that patients with damage affecting other frontal regions had difficulty with such trials, perhaps reflecting the role of the lateral and dorsomedial prefrontal cortices in attentional set-shifting (Dias et al, 1996;Vaidya and Fellows, 2016). Further work on the prefrontal mechanisms of individual attribute-value trade-offs in multiattribute choice is needed.…”
Section: Discussionmentioning
confidence: 84%
“…Our hypothesized view of vmPFC function is based on SUS-TAIN's formalism of highly interactive mechanisms of selective attention and learning 8 , functions theoretically mapped onto interactions between PFC and the hippocampus 9,28,32 . Support for this view is found in recent patient work that has demonstrated a causal link between attentional processes and vmPFC function in decision making [33][34][35] . These studies have shown that lesions to vmPFC disrupt attentional guidance based on prior experience with cue-reward associations 35 , learning the value of task-diagnostic features during probabilistic learning 33 , and value comparison during reinforcement learning 34 .…”
Section: Discussionmentioning
confidence: 92%
“…Support for this view is found in recent patient work that has demonstrated a causal link between attentional processes and vmPFC function in decision making [33][34][35] . These studies have shown that lesions to vmPFC disrupt attentional guidance based on prior experience with cue-reward associations 35 , learning the value of task-diagnostic features during probabilistic learning 33 , and value comparison during reinforcement learning 34 . These findings have been recently extended to healthy humans in a neuroimaging study which demonstrated that value signals in vmPFC are dynamically biased by attention during reinforcement learning 13 .…”
Section: Discussionmentioning
confidence: 92%